2011
DOI: 10.5114/aoms.2011.25557
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous renal biopsy of native kidneys: efficiency, safety and risk factors associated with major complications

Abstract: IntroductionThe use of an automated biopsy device and real-time ultrasound (current technology) for percutaneous renal biopsies (PRBs) has improved the likelihood of obtaining adequate tissue for diagnosis and has reduced the complications associated with renal biopsies. Our objective was to evaluate the efficacy and safety of the current PRB procedure and identify possible risk factors for the development of major complications.Material and methodsWe collected all native kidney PRBs performed with current tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
4
43
4
Order By: Relevance
“…The major bleeding complication rate in the present study (3.1%) is half those in the studies by Shidham et al (6) (6.2%) and Korbet et al (5) (6.6%) but slightly more than the rate in the study by Torres Munoz et al (19) (2.2%). Moreover, the risk of major bleeding complication in patients with SBP lower than 140 mm Hg and DBP lower than 90 mm Hg was less than 1% in the present study, compared with more than 5% in the study of Shidham et al (6).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The major bleeding complication rate in the present study (3.1%) is half those in the studies by Shidham et al (6) (6.2%) and Korbet et al (5) (6.6%) but slightly more than the rate in the study by Torres Munoz et al (19) (2.2%). Moreover, the risk of major bleeding complication in patients with SBP lower than 140 mm Hg and DBP lower than 90 mm Hg was less than 1% in the present study, compared with more than 5% in the study of Shidham et al (6).…”
Section: Discussioncontrasting
confidence: 56%
“…Likewise, major bleeding complications occurred more frequently in patients with higher versus lower DBP (8.7% for DBP 4 90 mm Hg vs 5.2% for DBP o 90 mm Hg), but that stratification also did not show a significant difference between the groups (P ¼ .11). Two more recent studies (5,19) have also shown an effect of SBP on the rate of bleeding complications after native renal biopsy. Torres Munoz et al (19) analyzed risk factors for 14 major complications that occurred in 2.2% of 623 native renal biopsies performed with realtime US guidance using automated biopsy devices; a DBP higher than 90 mm Hg conferred an OR of 7.6 (95% CI, 1.35-43) for major complications.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A higher transfusion rate was also found when compared to previously reported studies (9 vs. 0.4-6%) [19,20,21,22]. Indeed, a large number of patients had a low Hb concentration prior to biopsy as a mild decrease in Hb can lead to transfusion and a low Hb itself might be a risk factor for bleeding [11].…”
Section: Discussionmentioning
confidence: 66%
“…Although AKI patients are notoriously at high risk for post-biopsy bleeding [88,89] , in subjects with no evidence of pre-renal or obstructive diseases, the benefits of renal biopsy may outweigh the risks as the histological diagnosis might be useful to guide therapy and to predict outcomes.…”
Section: Acute Kidney Injurymentioning
confidence: 99%